Growth and Institutions in African Development - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2015)
Edited by Augustin K. Fosu Routledge Studies in Development Economics, 2015, pp. 393 (Hardcover). Reviewed by Simplice A. Asongu African Governance and Development Institute P.O. Box 8413, Yaoundé, Cameroon.
Keywords: D70; H10; O10; O55; 330; Growth; Institutions; Africa